Biomechanical Comparison of Distal Radioulnar Joint Reconstruction Graft Preparation Techniques - Li, Yibo; Beaudry, Eric; Besada, Nader; Chan, Robert; Westover, Lindsey (Journal of Wrist Surgery, 2023)
Background Graft preparation techniques for the Adams–Berger distal radioulnar joint (DRUJ) reconstruction vary among surgeons with insufficient evidence to support any specific technique.Questions/Purposes We compared survival with cyclic loading, absolute elongation, elongation rate, and modes of failure of four graft preparation techniques.Methods Fifteen porcine extensor tendons were divided into three equal groups: tendon only; tendon augmented along its full length with nonlocking 2–0 FiberLoop suture spaced at 6 mm intervals; and tendon with suture at 12 mm intervals. Suture only was also tested. Samples were woven through custom radius- and ulna-simulating jigs mounted on a mechanical testing machine. Samples underwent a staircase cyclic loading protocol and were then inspected visually for the mode of failure. Survival with cyclic loading, absolute elongation, and elongation rate was compared.Results Average survival with cyclic loading of suture-augmented tendon was significantly higher than tendon only. All tendon groups had significantly higher survival compared with suture only. Absolute elongation was subject to variability due to initial nonlinear elongation behavior of samples. The elongation rate was significantly lower with suture compared with all tendon groups. Modes of failure included rupture of the tendon and/or suture at the simulated graft–bone interface and elongation of the entire construct without rupture.Conclusions In this biomechanical study, augmentation of porcine tendons with suture spaced at either 6 or 12 mm for DRUJ reconstruction significantly increased survival to a staircase cyclic loading protocolClinical Relevance For the Adams–Berger reconstruction, tendon grafts augmented along their entire length by nonabsorbable braided suture are biomechanically superior to tendon alone.
Keywords: biomechanical testing; distal radioulnar joint reconstruction; tendon graft fixation